Isolation, purification, and kinetic study of lactate dehydrogenase from porcine skeletal and cardiac muscle tissues - Pangilinan, Cedric M. (Animo Repository, 2006)
Lactate dehydrogenase or LDH (EC. 1.1.1.27), an anaerobic glycolysis enzyme present in all vertebrates, was isolated from the skeletal and heart muscle tissues of domestic pig, Sus scrofa cristatus. The crude sample was purified using a series of techniques including centrifugation, dialysis, and salt precipitation. Further purification process in the form of gel filtration chromatography was carried out in the last stage to maximize the degree of purity of the enzyme. At each stage of purification, specific enzyme and protein concentration assays, employing the principles of ultraviolet (UV) absorption spectroscopy, were applied to each fraction collected in order to determine the degree of purification thus attained using the specified technique. The last fraction obtained, which was the enzyme fraction with the highest level of purity, was finally subjected to a kinetic study for the determination of parameters like Michaelis constant, maximum velocity, catalytic constant, and catalytic efficiency.